Dependence on plasma shape and plasma fueling for small edge-localized mode regimes in TCV and ASDEX Upgrade*In the future we will refer to the author list of the paper as the EUROfusion MST1 Team. (26th June 2019) - Labit, B.; Eich, T.; Harrer, G.F.; Wolfrum, E.; Bernert, M.; Dunne, M.G.; Frassinetti, L.; Hennequin, P.; Maurizio, R.; Merle, A.; Meyer, H.; Saarelma, S.; et al.
Abstract: Within the EUROfusion MST1 work package, a series of experiments has been conducted on AUG and TCV devices to disentangle the role of plasma fueling and plasma shape for the onset of small ELM regimes. On both devices, small ELM regimes with high confinement are achieved if and only if two conditions are fulfilled at the same time. Firstly, the plasma density at the separatrix must be large enough ( ), leading to a pressure profile flattening at the separatrix, which stabilizes type-I ELMs. Secondly, the magnetic configuration has to be close to a double null (DN), leading to a reduction of the magnetic shear in the extreme vicinity of the separatrix. As a consequence, its stabilizing effect on ballooning modes is weakened.